Health Information–Seeking Behaviors, Health Indicators, and Health Risks - Weaver, James B.; Mays, Darren; Weaver, Stephanie Sargent; Hopkins, Gary L.; Eroğlu, Doğan; Bernhardt, Jay M. (American journal of public health (1971), 2010)
Objectives. We examined how different types of health information–seeking behaviors (HISBs)—no use, illness information only, wellness information only, and illness and wellness information combined—are associated with health risk factors and health indicators to determine possible motives for health information seeking. Methods. A sample of 559 Seattle–Tacoma area adults completed an Internet-based survey in summer 2006. The survey assessed types of HISB, physical and mental health indicators, health risks, and several covariates. Covariate-adjusted linear and logistic regression models were computed. Results. Almost half (49.4%) of the sample reported HISBs. Most HISBs (40.6%) involved seeking a combination of illness and wellness information, but both illness-only (28.6%) and wellness-only (30.8%) HISBs were also widespread. Wellness-only information seekers reported the most positive health assessments and the lowest occurrence of health risk factors. An opposite pattern emerged for illness-only information seekers. Conclusions. Our findings reveal a unique pattern of linkages between the type of health information sought (wellness, illness, and so on) and health self-assessment among adult Internet users in western Washington State. These associations suggest that distinct health motives may underlie HISB, a phenomenon frequently overlooked in previous research.